Result of research and professional nursing practice - Cardoso, Maria Vera Lúcia Moreira Leitão (Rev Rene, 2010)
It is highly distinctive the team effort of those who intend to work to make public the results and knowledge investigated in the research in the nursing area, whether in the form of articles, abstracts of Annals of events, interviews, scientific and technical meetings or even in the intramurals of universities as well as research groups. We seek to externalize what, now, tends to portray what we are today. However, there is still a lot to be revealed, analyzed, and socialized. There is a necessity to evaluate the impact of this knowledge in the continuum of care to the human being as a focus for a practice which is more based on a body of knowledge which is consistent and coherent with our reality. DOI: https://doi.org/10.15253/2175-6783.2010000200001